Efficacy of Novel Endoillumination Assisted Modified Scleral Buckling versus Conventional Scleral Buckling - Asif Ali, Naseer Ahmad, Faisal Nawaz, Abdul Munim, Abdul Rafe, Haroon Saleem, Mir Ali Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Scleral buckling (SB) has proven to be an effective surgical technique for RRDs especially in patients with uncomplicated rhegmatogenous retinal detachment (RRD) not associated with proliferative vitreoretinopathy (PVR). Until recently, it was still the most commonly employed surgical technique in dealing with RRDs with a high success rate. with the advent of the modern retinal viewing systems and vitrectomy machines, the trends in dealing with RRD are more inclining towards pars plana vitrectomy. Possible reasons for it are that conventional SB has steeper learning curve and it is assisted by the Indirect ophthalmoscope to view the retina during various steps of the surgery which has smaller inverted image and also its use is cumbersome. with the novel techniques being introduced, the essence of scleral buckling can be preserved and the surgical technique can be made much easier by providing a better viewwith easy localization of retinal breaks. The basic principles and steps of conventional scleral buckling can be well taught and more effectively practiced with the introduction of better illumination and viewing systems. In this study, the efficacy of endoillumination source assisted modified scleral buckling would be determined and compared with the results of conventional scleral buckling. Objective: To compare the functional and anatomical success rates of conventional scleral buckling for RRD with endo-illumination assisted Wide angle viewing system modified scleral buckling in patients with uncomplicated rhegmatogenous retinal detachment. Materials and Methods: This is an interventional prospective study being conducted at the Department of Ophthalmology, Peshawar Medical College (PMC) and Allied hospitals from July 1, 2020 to December 31, 2020. The study included 40 patients presenting with uncomplicated RRD, 20 in each group, by simple random sampling technique. Outcome measures assessed were primary visual acuity (VA), primary anatomical success, and peri-operative complications. Results: 40 patients (40 eyes) were recruited in this study, 20 in each group (conventional scleral buckling group and modified scleral buckling group), who completed a 3 months follow up. 21 (52.5%) were male patients while 19 (47.5%) patients were female. Mean age was 44.3 ± 12.1. New retinal breaks were identified in 3(15%) patients in the MSB group. Retinal reattachment was achieved in 95% patients in both the groups. Cataract Progression was later found in 1(5%) patient in the MSB group. No other complications were recorded in either of the comparative groups. 1(5%) patient each, in both the groups, underwent additional surgeries. Conclusion: In conclusion, the endolight-assisted scleral buckling using a wide angle visualization system appears to be a promising technique with comparable surgical outcomes to conventional scleral buckling with least complications in specific cases of rhegmatogenous retinal detachment. It can be safely used to meet the surgical need and reduce discomfort during surgery. It is particularly useful in cases with pre-operatively undetected retinal tears. Wide angle viewing system assisted modified scleral buckling technique is highly recommended for teaching purposes. Keywords: Scleral buckling; Wide angle viewing system, Rhegmatogenous retinal detachment, Modified scleral buckling.